Illness anxiety disorder and somatic symptom disorder: Similarities and differences in health-anxious individuals - Katarina Kikas; Emily Upton; Brittany Corkish; Aliza Werner-Seidler; Jill M. Newby (PLoS ONE, 2026)
Little is known about the features and characteristics of illness anxiety disorder (IAD) and somatic symptom disorder (SSD), and whether the minimal somatic symptom requirement in IAD is valid and useful. This study compares IAD and SSD, and IAD (involving no or mild somatic symptoms) to a modified IAD diagnosis (modified to include moderate-to-severe somatic symptoms) in health anxious individuals. We recruited health anxious individuals drawn from the community and assessed IAD and SSD. We compared the disorders on demographic and clinical characteristics, health care utilization, and assessed the prevalence of IAD subtypes. The validity of the IAD somatic symptom criterion was examined by comparing current IAD with modified IAD. Among 118 participants, 28 met criteria for IAD, 47 for SSD, and 38 for modified IAD. Most with IAD fluctuated between seeking and avoiding medical care (71.4%), while 25% were care-seeking and 3.6% were care-avoidant. Demographic information, illness course, mental health comorbidities, and symptom severity did not differ significantly between IAD and SSD. However, individuals with SSD reported significantly more somatic symptoms, chronic health conditions, reduced quality of life, and more health care visits compared to individuals with IAD. Similar findings were observed between IAD-current and IAD-modified. The minimal differences between IAD and SSD, and between IAD-current and IAD-modified call into question the utility of distinguishing health anxiety presentations based on somatic symptom presence and severity. Further research should compare these disorders on illness course and treatment outcomes.